The health and economic burden of smoking in 12 Latin American countries and the potential effect of increasing tobacco taxes: an economic modelling study. Issue 10 (October 2020) - Pichon-Riviere, Andrés; Alcaraz, Andrea; Palacios, Alfredo; Rodríguez, Belén; Reynales-Shigematsu, Luz Myriam; Pinto, Márcia; Castillo-Riquelme, Marianela; Peña Torres, Esperanza; Osorio, Diana Isabel; Huayanay, Leandro; Loza Munarriz, Cesar; de Miera-Juárez, Belén Sáenz; et al.
Summary: Background: Worldwide, smoking tobacco causes 7 million deaths annually, and this toll is expected to increase, especially in low-income and middle-income countries. In Latin America, smoking is a leading risk factor for death and disability, contributes to poverty, and imposes an economic burden on health systems. Despite being one of the most effective measures to reduce smoking, tobacco taxation is underused and cigarettes are more affordable in Latin America than in other regions. Our aim was to estimate the tobacco-attributable burden on mortality, disease incidence, quality of life lost, and medical costs in 12 Latin American countries, and the expected health and economic effects of increasing tobacco taxes. Methods: In this modelling study, we developed a Markov probabilistic microsimulation economic model of the natural history, medical costs, and quality-of-life losses associated with the most common tobacco-related diseases in 12 countries in Latin America. Data inputs were obtained through a literature review, vital statistics, and hospital databases from each country: Argentina, Bolivia, Brazil, Chile, Colombia, Costa Rica, Ecuador, Honduras, Mexico, Paraguay, Peru, and Uruguay. The main outcomes of the model are life-years, quality-adjusted life-years, disease events, hospitalisations, disease incidence, disease cost, and healthy years of life lost. We estimated direct medical costs for each tobacco-related disease included in the model using a common costing methodology for each country. The disease burden was estimated as the difference in disease events, deaths, and associated costs between the results predicted by the model for current smoking prevalence and a hypothetical cohort of people in each country who had never smoked. The model estimates the health and financial effects of a price increase of cigarettes through taxes, in terms of disease and health-care costs averted, and increased tax revenues. Findings: In the 12 Latin American countries analysed, we estimated that smoking is responsible for approximately 345 000 (12%) of the total 2 860 921 adult deaths, 2·21 million disease events, 8·77 million healthy years of life lost, and $26·9 billion in direct medical costs annually. Health-care costs attributable to smoking were estimated to represent 6·9% of the health budgets of these countries, equivalent to 0·6% of their gross domestic product. Tax revenues from cigarette sales cover 36·0% of the estimated health expenditures caused by smoking. We estimated that a 50% increase in cigarette price through taxation would avert more than 300 000 deaths, 1·3 million disease events, gain 9 million healthy life-years, and save $26·7 billion in health-care costs in the next 10 years, with a total economic benefit of $43·7 billion. Interpretation: Smoking represents a substantial health and economic burden in these 12 countries of Latin America. Tobacco tax increases could successfully avert deaths and disability, reduce health-care spending, and increase tax revenues, resulting in large net economic benefits. Funding: International Development Research Centre (IDRC), Canada. Translations: For the Portuguese and Spanish translations of the abstract see Supplementary Materials section.